PENINGKATAN PEMBANGKIT LISTRIK UNTUK DAERAH TERPENCIL BERBASISKAN TURBIN CROSS-FLOW 1KW - Nanang Purnomo; Adi Sastra P Tarigan; Solly Aryza (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
MHP (Microhydro Power Plant) was built after going through a thorough feasibility study with parameters: water discharge, height, type of generator and others, so that when given a maximum load, the generator is still able to produce voltage and frequency according to the standard. However, MHP has not been utilized optimally so that changes in the load on consumers cause voltage and frequency fluctuations because the generator speed will tend to change too, and in reality the changes that occur cannot be monitored at any time. Changes in load that often occur in a PLTMH can cause frequency stability to be disturbed. It can also cause the wheels to spin faster. In this study discusses the support for the performance of this MHP, setting or controlling the frequency is very necessary so that it is always in the working area between 49 Hz - 51 Hz. The purpose of this paper is to design an electronic load divider control system using a firing angle control on a micro hydro power generator (PLTMH), so that the load from the generator in this case is the consumer's load is not damaged by using the ATMega 16 microcontroller.Keywords: MHP, New Method, Frequency stability.